PV Microinverters: Latest Efficiency Rankings, Energy Yield Assessments, Firmware Issues - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

Lifelogging in einer Kultur der Digitalität. Analysen aus der medienkompetenztheoretischen Perspektive Dieter Baackes. - Dehmel, Lukas; Burgfeld-Meise, Bianca (Ludwigsburger Beiträge zur Medienpädagogik)

Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Solid solutions of lithium niobate and lithium tantalate: crystal growth and the ferroelectric transition - Bashir, Umar; Böttcher, Klaus; Klimm, Detlef; Ganschow, Steffen; Bernhardt, Felix; Sanna, Simone; Rüsing, Michael; Eng, Lukas M.; Bickermann, Matthias (Ferroelectrics)
Specific heat capacity measurements by differential scanning calorimetry (DSC) of single crystals of solid solutions of LiNbO3 and LiTaO3 are reported and compared with corresponding ab initio calculations, with the aim to investigate the variation of the ferroelectric Curie temperature as a function of composition. For this purpose, single crystals of these solid solutions were grown with Czochralski pulling along the c-axis. Elemental composition of Nb and Ta was investigated using XRF analysis, and small samples with homogeneous and well known composition were used for the DSC measurements. We observed that the ferroelectric Curie temperature decreases linearly with increasing Ta concentration in the LiNb1−x Tax O3 solid solution crystals. Furthermore, the ferroelectric transition width of a mixed crystal appears to be smaller, as compared to pure LiTaO3.
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Learning the pronunciation of segmental features of english phonology at german primary schools - Hahn, Charlotte Anna
In der vorliegenden Arbeit wird die Auswirkung expliziter Ausspracheübungen auf die englische Aussprache von Kindern an Grundschulen in NRW untersucht. Das Ziel dieser Arbeit ist es, eine Alternative für den mittel-offenen vorderen Vokal /æ/ und die dentalen Frikative /, ð/ zu bieten. Es wurde eine Interventionsstudie mit 72 Teilnehmenden aus drei verschiedenen Grundschulklassen durchgeführt; zwei vierte Klassen mit verschiedenen Lehrkräften und eine dritte Klasse, die von der Lehrperson einer der vierten Klassen unterrichtet wurde. Jede Klasse wurde in eine Kontroll- und zwei Interventionsgruppen (je eine für den Vokal und die Konsonanten) geteilt. Alle Gruppen wurden einmal zu Beginn und zwei Mal am Ende der Studie getestet. Zwischen den letzten beiden Tests lagen sechs bis acht Wochen, um einen mittelfristigen Effekt zu testen. Die Intervention, die nach der ersten Messung stattfand, wurde auf zwei je ca. drei-minütige Einzelsitzungen aufgeteilt. Während der Intervention übten die Teilnehmenden mit der Autorin die Aussprache des relevanten Phonems. Die Ergebnisse dieser Studie zeigen, dass die Interventionen einen Effekt auf die Aussprache der Teilnehmenden hatten. Wie sich dieser Effekt verhält und entwickelt scheint von der Art des Phonems, dem Alter der Teilnehmenden sowie der bisherigen Ausspracheschulung abzuhängen. Die vorliegenden Ergebnisse liefern Erkenntnisse nicht nur für die Grundschule selbst, sondern auch für die Lehrer*innenausbildung und Lehrplanentwicklung.

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Systematics for an Integrative Modelling of Product and Production System - Schäfer, Louis; Günther, Matthias; Martin, Alex; Lüpfert, Mariella; Mandel, Constantin; Rapp, Simon; Lanza, Gisela; Anacker, Harald; Albers, Albert; Köchling, Daniel (Procedia CIRP)
Keywords: General Medicine

Virtual Assembly for Engineering – A Systematic Literature Review - Dyck, Florian; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Reibungsinduzierter Prozess zum nutzerindividuellen und energieeffizienten Recycling von Aluminiumschrotten - Borgert, Thomas
Die weltweit erzeugten Emissionen müssen in allen emittierenden Sektoren signifikant gesenkt werden, um die Auswirkungen des Klimawandels zu reduzieren. Dies ist unter anderem durch die energieeffiziente Wiederverwertung vorhandener Ressourcen und damit der Einstellung einer nachhaltigen Kreislaufwirtschaft möglich. Aufgrund der hohen erforderlichen Energiemenge in der primären Herstellung von Aluminium existieren hier im Vergleich zu anderen Konstruktionswerkstoffen große Einsparpotentiale. Mit dem in dieser Arbeit erforschten reibungsinduzierten Recyclingverfahren (RIR) wird eine alternative und energieeffiziente Prozessroute zum direkten Recycling von unterschiedlichen Aluminiumschrotten geschaffen. Zur Charakterisierung der Prozessroute werden u. a. die Erkenntnisse aus sich gegenseitig unterstützenden experimentellen und theoretischen Untersuchungen zu den Vorgängen der der Verdichtung, Plastifizierung als auch Extrusion der recycelten Profile dargelegt. Die Einflüsse unterschiedlicher Eingangsgrößen wie z. B. der Werkzeuggestaltung oder der Verarbeitung unterschiedlicher Legierungen werden zudem zur zukünftigen Auslegung des Prozesses erläutert. Aus der abschließenden energetischen Bilanzierung kann geschlossen werden, dass aufgrund der geringeren Verarbeitungstemperatur signifikante Energieersparnisse bei Verwendung des RIR im Vergleich zu den konventionellen Produktionsstrategien erzielt werden können.

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

Erlebnisorientiert Lehren und Lernen in der beruflichen Bildung. Entwicklung eines didaktischen Konzepts im Rahmen von designbasierter Forschung. - Volgmann, Simone

Minisymposium Data Science - Podworny, Susanne; Frischemeier, Daniel (Beiträge zum Mathematikunterricht 2022: 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 29.08.2022 bis 02.09.2022 in Frankfurt am Main)

A Social Network Approach for Investigating Social Influences on Effective Use: Demonstration in Virtual Reality Collaboration - Tölle, Laura; Slawinski, Elena; Fromm, Jennifer; Mirbabaie, Milad

Under Pressure? - The Effect of Conversational Agents on Task Pressure and Social Relatedness in Digital Labor - Lichtenberg, Sascha; Hildebrandt, Fabian; Mirbabaie, Milad

Understanding Digital Nomadism as an Employer Branding Signal - Marx, Julian; Langer, Marie; Mirbabaie, Milad

Model Predictive Direct Self-Control for Six-Step Operation of Permanent-Magnet Synchronous Machines - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Differentially Private Natural Language Models: Recent Advances and Future Directions

How Much User Context Do We Need? Privacy by Design in Mental Health NLP Applications - Sawhney, Ramit; Neerkaje, Atula; Habernal, Ivan; Flek, Lucie (Proceedings of the International AAAI Conference on Web and Social Media)
Clinical NLP tasks such as mental health assessment from text, must take social constraints into account - the performance maximization must be constrained by the utmost importance of guaranteeing privacy of user data. Consumer protection regulations, such as GDPR, generally handle privacy by restricting data availability, such as requiring to limit user data to 'what is necessary' for a given purpose. In this work, we reason that providing stricter formal privacy guarantees, while increasing the volume of user data in the model, in most cases increases benefit for all parties involved, especially for the user. We demonstrate our arguments on two existing suicide risk assessment datasets of Twitter and Reddit posts. We present the first analysis juxtaposing user history length and differential privacy budgets and elaborate how modeling additional user context enables utility preservation while maintaining acceptable user privacy guarantees.

One size does not fit all: Investigating strategies for differentially-private learning across NLP tasks - Senge, Manuel; Igamberdiev, Timour; Habernal, Ivan (Proceedings of the 2022 Conference on Empirical Methods in Natural Language Processing)

DP-BART for Privatized Text Rewriting under Local Differential Privacy - Igamberdiev, Timour; Habernal, Ivan (Findings of the Association for Computational Linguistics: ACL 2023)